Predicting prognosis of post-chemotherapy patients with resected IIIA non-small cell lung cancer - Zheng, Difan; Wang, Yiyang; Li, Yuan; Sun, Yihua; Chen, Haiquan (Journal of Thoracic Disease; Vol 10, No 7 (July 31, 2018): Journal of Thoracic Disease, 2018)
Background: Recently, nomogram has been widely used in cancer prognoses. However, the predicting model for post-chemotherapy patients with resected IIIA non-small cell lung cancer (NSCLC) still remains scarce. Here, we tried to develop nomograms for predicting the recurrence and survival of these patients. Methods: We retrospectively analyzed our database from October 2007 to May 2013 at Fudan University Shanghai Cancer Center. 437 qualified patients were included. Univariable and multivariable analyses of cox regression were performed successively to select prognostic factors and nomograms for recurrence-free survival (RFS) and overall survival (OS) were developed. Concordance indexes (C-index) and calibration curves were created to measure the consistency between predicted and actual survivals. Finally, risk group stratifications according to risk scores calculated from nomograms were delineated. Results: With a total of 437 patients, five independent prognostic factors related to RFS and two to OS were selected to develop nomograms, respectively. Both 3- and 5-year RFS and OS calibration curves indicated a moderate concordance between the predicted and actual outcomes, consisted with the C-index 0.656 (95% CI: 0.626–0.687) for RFS and 0.651 (95% CI: 0.611–0.691) for OS. Different risk groups showed significant differences in RFS and OS. Conclusions: We developed nomograms of RFS and OS for predicting recurrence and survival of post-chemotherapy patients with resected IIIA NSCLC. These nomograms could help doctors more easily estimate the prognosis and choose optimal decisions for individual during clinical practices.